Judicial Trend in Contract Related Disputes: Nepalese Perspective - Giri, Saroj Kumar (Dristikon: A Multidisciplinary Journal, 2024)
This research delves into the dynamic evolution of contract law in Nepal over the past five and a half decades, focusing on the pivotal role played by the Supreme Court. The study analyzes the major changes in contract-related decisions and identifies emerging trends shaping Nepal's legal landscape. Beginning with Nepal's initial contract regulations under Ain and tracing the legal journey through various legislative acts, the study scrutinizes key Supreme Court cases that have defined and refined the understanding of contracts. The research highlights the transformative trends in Nepal's contract law. Furthermore, the study explores the issue of contract validity. In addition, the research examines the critical demarcation between civil and criminal jurisdiction in contractual matters. Through the various cases, Supreme Court of Nepal developed the doctrine that contractual disputes lacking criminal elements fall under civil jurisdiction, preventing unwarranted criminalization of contractual disagreements and ensuring a balanced legal approach. Thus, the article argues that comprehensive analysis through the various cases, Supreme Court of Nepal illuminates Nepal's progressive legal framework in contracts, promoting transparency, fairness, and adherence to fundamental legal principles. The research contributes valuable insights into the evolution of Nepal's contract law, providing a foundation for fostering a favorable business environment in the country.